A five-year follow-up of the verbal memory performance of individuals with bipolar disorder and schizophrenia: evidence of unchanging deficits under treatment. Issue 1 (2nd January 2023) - Martins, Dayane Santos; Hasse-Sousa, Mathias; Reckziegel, Ramiro de Freitas Xavier; Lapa, Clara de Olivera; Petry-Perin, Carolina; Britto, Maria Julia; Remus, Isadora Bosini; Gama, Clarissa Severino; Czepielewski, Leticia Sanguinetti
ABSTRACT: Objective: Bipolar disorder (BD) and schizophrenia (SZ) are chronic and heterogeneous mental disorders that present cognitive and functional impairments. Verbal memory is considered an important predictor of functioning and a domain vulnerable to the aging process. However, only few studies investigate the progression of memory longitudinally in BD and SZ, especially in lower- and middle-income countries. Therefore, we aim to evaluate the course of verbal memory in individuals with BD and SZ. Methods: We assessed 31 individuals with BD and 27 individuals with SZ under treatment at outpatient clinics at baseline and after five years. They were assessed through a sociodemographic questionnaire, memory and estimated IQ (eIQ) instruments, and clinical scales. Results: Individuals with SZ showed worse verbal memory performance in comparison to BD, however, we did not observe changes over time within patient groups. Individuals with BD with higher eIQ showed a better verbal memory performance, while no effect of eIQ was found for subjects with SZ. Conclusion: Patients with SZ and BD showed different levels of verbal memory impairment, although they had similar unchanging trajectories after 5 years under psychiatric treatment. This finding indicates a relative stable cognitive course for both disorders.